Childhood obesity and endocrine disrupting chemicals - Jin Taek Kim; Hong Kyu Lee (Korean Society of Pediatric Endocrinology, 2017)
The prevalence of obesity around the world has increased sharply. Strong evidence has emerged over the last decades that human exposure to numerous endocrine disrupting chemicals (EDCs) is the cause of obesity and obesity-related metabolic diseases. Many EDCs are manmade chemicals that are released into the environment. EDCs are exogenous compounds that interfere with hormonal regulation and normal endocrine systems, thereby affecting the health of animals and humans. The number of chemicals belonging to EDCs is increasing and some of them are very stable; they persist in the environment (persistent organic pollutants). Although they are banned, their concentrations have been continuously increasing over time. This review gives a brief introduction to common EDCs, and evidence of harmful effects of EDCs on obesity-related diseases; we focus in particular on EDCs' role in causing mitochondrial dysfunction.